A Longitudinal Approach to Climate Change Vulnerability Assessment in Ulukhaktok, NT - Fawcett, David (University of Guelph, 2017)
This thesis develops longitudinal approaches to vulnerability research, and applies one of these approaches to assess vulnerability to climate change among Inuit in Ulukhaktok, Northwest Territories. This research expands on previous research on climate change impacts, adaptation, and vulnerability in the Arctic to contribute to a growing body of scholarship focused on understanding the dynamism of vulnerability and adaptation. Data were collected using semistructured interviews with Inuit (n=32), participant observation, and analysis of secondary sources. The findings were comparatively analyzed with those from data collected in Ulukhaktok in 2005 and other longitudinal datasets. The results indicate that climatic stresses documented in 2005 to adversely affect subsistence activities have persisted or progressed, and dynamic non-climatic processes, including, for example, access to income, time constraints due to wage employment, and the transmission of environmental knowledge and land skills condition how hunters experience and respond to climatic stresses. Entry points to support adaptation should focus on addressing a growing tension between the subsistence and wage economies, which has resulted in some adaptation trends that may lead to adaptation constraints in the future. ArcticNet Canadian Institutes of Health Research Northern Scientific Training Program University of Guelph Aurora Research Institute University of Guelph